"The meal is an activity involving at least two people"-Experiences of meals by older persons in need of elderly care - Sigrid Odencrants; Karin Blomberg; Anne‐Marie Wallin (Wiley, 2020)
Abstract Aim A shift of focus on older persons' nutrition has occurred, from focusing on nutrition status to focusing on the whole meal. There is lack of studies on how older persons experience meals. Knowledge is needed to enhance a meal with dignity and pleasure, but also to prevent deterioration in nutrition. The aim was to describe meals from the perspective of older persons in need of elderly care. Design A descriptive qualitative study. Method Semi‐structured interviews (N = 18) were conducted and analysed using thematic analyses. Result Three themes were identified: The meal is an activity which involves at least two persons, The meal relates to habits and traditions and The meal seldom gives possibilities to make individual choices. It was obvious that older persons who live in nursing homes miss the opportunity to decide what to eat, when to eat and with whom to eat. Attention must be paid to listening to older persons to enhance mealtime with dignity and autonomy.